TINJAUAN GEOGRAFIS KEBERADAAN INDUSTRI KERUPUK UDANG - Kiki Kurniawan; Budiyono Budiyono; Nani Suwarni (JPG (Jurnal Penelitian Geografi), 2013)
This study aims to describe the state of shrimp Crackers Industry Geographic Existence In Rural District Purwodadi Trimurjo Central Lampung regency in 2012. Ease pressure point research of study : received easiness materials, labor, availability of water, availability of energy sources, transportation, and marketing of products. This study uses descriptive metode. This study population as much as 7 businessman shrimp crackers. Data collection by observation, structured interviews, and documentation. Analysis of data with a table percentage, as the basis for interpretation and description in reporting research results. These results indicate: (1) all states responden easily obtain raw materials, (2) easily obtain employment, (3) easily obtain the water, (4) easily obtain the energy source, (5) easily obtain the means of transportation, (6) as much as (85.7%) marketing of products easily and sold out. Keywords : Existence, easiness, businessman